Analysis of the Application of Environmental Accounting in Improving Financial Performance at PDP Kahyangan Gunung Pasang, Panti District, Jember - Suprianik; Devina Ayu Trisna (Journal of Creative Power and Ambition (JCPA), 2026)
The increasing development of industry, especially in the manufacturing sector, has a direct impact on the environment from its operational activities. One effort that companies can make to reduce these negative impacts is by implementing environmental accounting. This study aims to determine: (1) The application of environmental accounting in improving financial performance at PDP Kahyangan Gunung Pasang; (2) What factors support and hinder the implementation of environmental accounting at PDP Kahyangan Gunung Pasang; (3) The impact of the implementation of environmental accounting on the company. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. Data analysis is carried out by data reduction, data presentation, and drawing conclusions. The results of the study show that PDP Kahyangan Kebun Gunung Pasang has implemented environmental accounting practices through waste management and environmental cost expenditures, but has not been recorded specifically in the financial statements because it is still combined with the company's operational costs. Supporting factors for the implementation of environmental accounting are the company's awareness of the importance of environmental sustainability and compliance with regulations, while inhibiting factors are limited human resources and the absence of a structured environmental cost reporting system. The implementation of environmental accounting has a positive impact on cost efficiency, environmental risk control, and increased stakeholder trust, thereby supporting improved company financial performance.